DIFFICULTIES IN OVERCOMING VOCABULARY LEARNING PROBLEMS IN 7TH GRADE STUDENTS - Muborak, Hotimatova (Research Focus International Scientific Journal, 2026)
In recent years, learning new vocabulary has become important because it plays a key role in improving students’ language skills. However, there is limited research on the specific difficulties faced by 7th-grade students in learning new words. The study employed a qualitative design. The participants were 15 seventh-grade students from a secondary school. Data were collected through questionnaires and classroom observations and analyzed using thematic analysis. The findings indicate that students struggle with memorizing and using new words in context. The results also show that a lack of practice and motivation affects their vocabulary learning. The study suggests that interactive methods, different kinds of flashcards, and regular practice can improve vocabulary learning. These findings have implications for teachers and students in enhancing effective vocabulary teaching strategies.